The views of students in the 14-19 phase attending three special schools and a secure unit on their learning and achievement (UCL Press, 2013)
The involvement of special schools and centres in curriculum policy initiatives has been remarkably limited both in the UK and internationally, and research investigating students' perspectives on the curriculum and teaching and learning in such centres is practically non-existent. The views of students on curriculum and pedagogy attending three special schools and a secure unit are explored and four key themes that emerged are discussed. It is proposed that aspects of the provision at the four special centres contribute to inclusive education practices.